The Tragedy Cimareme: The Resistance of Haji Hasan to the Colonial Power in 1919 - Hajati, Chusnul (Studia Islamika, 1996)
History records "Cimareme events" as one of the important events during the year 1919 in Indonesia. This event is the culmination of resistance Cimareme villagers, led by Haji Hasan, against the Dutch colonial government.The key drivers of this event is more economical interests. A year before the incident erupted, the Dutch colonial government set the rules for the purchase of paddy indigenous farmers. This step was taken to address food shortages due to crop failures and difficulties imports.Rules set by the government rice purchase is deemed unfair by Haji Hasan. The government requires that farmers in other regions to only sell them as two measures of rice per smell land, while farmers are required to sell their rice two times more than that number. Hajj Hasan questioned this rule, and determined not to sell rice to the government. This attitude then cause conflicts with local indigenous officials, and finally the Dutch colonial government took strong action through the raid.DOI: 10.15408/sdi.v3i2.807